2021
DOI: 10.1038/s41598-021-91005-9
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized dermis extracellular matrix alloderm mechanically strengthens biological engineered tunica adventitia-based blood vessels

Abstract: The ideal engineered vascular graft would utilize human-derived materials to minimize foreign body response and tissue rejection. Current biological engineered blood vessels (BEBVs) inherently lack the structure required for implantation. We hypothesized that an ECM material would provide the structure needed. Skin dermis ECM is commonly used in reconstructive surgeries, is commercially available and FDA-approved. We evaluated the commercially-available decellularized skin dermis ECM Alloderm for efficacy in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Comercially available human decellularized dermal matrix (Glyaderm) was shown to enhance re-epithelialization and healed full thickness skin defects when seeded with adipose derived stem cells (ASC) in murine wound models . Similarly, AlloDerm, provided structure and support to biologically engineered blood vessels which were mechanically stronger than vessels lacking AlloDerm ECM . The group of da Mata Martins et al demonstrated the importance of choosing appropriate decellularizing techniques to preserve the ultrastructures of decellularized human cornea where the epithelial BM (EBM) was preserved.…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 93%
See 2 more Smart Citations
“…Comercially available human decellularized dermal matrix (Glyaderm) was shown to enhance re-epithelialization and healed full thickness skin defects when seeded with adipose derived stem cells (ASC) in murine wound models . Similarly, AlloDerm, provided structure and support to biologically engineered blood vessels which were mechanically stronger than vessels lacking AlloDerm ECM . The group of da Mata Martins et al demonstrated the importance of choosing appropriate decellularizing techniques to preserve the ultrastructures of decellularized human cornea where the epithelial BM (EBM) was preserved.…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 93%
“… 197 Similarly, AlloDerm, provided structure and support to biologically engineered blood vessels which were mechanically stronger than vessels lacking AlloDerm ECM. 183 The group of da Mata Martins et al demonstrated the importance of choosing appropriate decellularizing techniques to preserve the ultrastructures of decellularized human cornea where the epithelial BM (EBM) was preserved. This intact EBM structure was reported to differentiate the human embryonic stem cells to epithelial-like cells.…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main role of adventitia is to provide structural integrity to the whole vessel which includes collagen, ECMs, and fibroblasts. 28 , 29 On the other hand, media which is composed of smooth muscle cells (SMCs) and pericytes is the thickest layer among the three layers, and it renders load bearing capability. 30 Intima is an innermost layer of blood vessels which adjusts vascular tones and it is comprised of endothelial cells (ECs).…”
Section: Introductionmentioning
confidence: 99%
“…After decellularization, most of the cells, antigens, and other components would be removed. There are several successful cases for decellularized scaffolds including airway clinical transplantation [71] and more than 20 commercial products [72] (AlloDerm [73,74], AxoGen® [75], etc. )…”
Section: Having Good Biocompatibilitymentioning
confidence: 99%